ChemInform Abstract: Cross‐Coupling Reaction of a Highly Strained Molecule: Synthesis of σ—π Conjugated Tetrahedranes. Issue 10 (11th March 2014) - Kobayashi, Yuzuru; Nakamoto, Masaaki; Inagaki, Yusuke; Sekiguchi, Akira
Abstract Reaction of tetrakis(trimethylsilyl)tetrahedrane with MeLi produces a solution of tris(trimethylsilyl)tetrahydryl lithium which is easily amenable for Pd‐catalyzed cross‐coupling processes to produce thermally stable arylated tetrahedranes.